Implementation of Productive Alms in Increasing Social Welfare - m afif mastur (LP2M IAIN Palopo, 2023)
This research aims to answer 1) whether a form of productive alms implementation has been realized in improving social welfare at LAZISNU Tanggulangin and 2) how it affects social welfare in the Tanggulangin community environment. The type of research used in this research is qualitative research with a descriptive approach. In this research, data collection techniques used observation, interviews and document studies in the form of using sources from online articles regarding LAZISNU, Tanggulangin District. The research results obtained show that 1) The implementation of alms has been carried out in the form of basic necessities and social assistance. However, productive alms for social welfare in Tanggulangin has not been realized. 2) the influence of productive almsgiving on social welfare has not been affected because there has been no realization of the productive alms program.